Pengaruh Penilaian Kinerja Sumber Daya Manusia Terhadap Kepuasan Pasien dan Kualitas Pelayanan Pada RSUD Mardi Waluyo Blitar - Damayanti, Kristya; Prasetyorini, Ema; Farisma, Alicia Windy (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This research aims to examine the effect of human resource performance on service quality and patient satisfaction in the Dahlia Ward of RSUD Mardi Waluyo Blitar. The study adopts a quantitative survey approach, involving a sample of 30 patients. The key variables analyzed include human resource performance, service quality, and patient satisfaction. The findings demonstrate that human resource performance has a significant influence on both service quality and patient satisfaction. High-quality human resource performance leads to better service quality, ultimately increasing patient satisfaction.This study employs a quantitative methodology with a survey approach. Data were gathered using questionnaires distributed to 30 patients who received treatment in the Dahlia Ward of RSUD Mardi Waluyo. The analyzed variables consist of human resource performance (competence, responsibility, motivation), service quality (tangibility, reliability, responsiveness, assurance, empathy), and patient satisfaction.